Improving Science Learning Outcomes Through the Development of the Magic Card Box Learning Media - Framz Hardiansyah; Agus Wahdian (AL-ISHLAH: Jurnal Pendidikan, 2023)
One problem that often arises in science learning is the low enthusiasm of students to take part in learning, which impacts learning outcomes. The learning method used by the teacher is still reasonably monotonous. The solution is that teachers must innovate and be creative to increase student activity and enthusiasm for learning. One solution is to use learning media that can arouse students' enthusiasm. This study aims to produce science learning media, namely the magic card box for water cycle material, to determine the feasibility of learning media and students' understanding of the water cycle material. This research is development research using a 3-D model. Learning media of the magic card box is validated by material experts, media experts, and learning practitioner assessments. The development instrument is a questionnaire consisting of thirteen indicators distributed to 25 students as respondents. Learning Media The magic card box was tested on fifth-grade students. Validation data and data on the level of understanding of students' cognitive aspects were analyzed quantitatively. Learning media Magic card boxes are produced through the stages of defining, designing, and developing. According to media experts, the learning media feasibility test results obtained a final score of 4.2 with a very good category. Then in the field trial, a score of 4.82 was obtained in the very good category. Students' understanding of the water cycle material based on cognitive aspects obtained an average score of 81.1. Shows that the Magic Card Box Media on the water cycle material is valid, practical and can improve student learning outcomes.